Assessing the reliability and readability of migraine treatment information on Turkish websites - Tuba Tanyel Saraçoğlu; Gizem Gürsoy (BMC, 2024)
Abstract Background The quality and safety of information provided on online platforms for migraine treatment remains uncertain. We evaluated the top 10 trending websites accessed annually by Turkish patients seeking solutions for migraine treatment and assessed information quality, security, and readability in this cross-sectional study. Methods A comprehensive search strategy was conducted using Google starting in 2015, considering Türkiye's internet usage trends. Websites were evaluated using the DISCERN measurement tool and Ateşman Turkish readability index. Results Ninety websites were evaluated between 2015 and 2024. According to the DISCERN measurement tool, most websites exhibited low quality and security levels. Readability analysis showed that half of the websites were understandable by readers with 9th − 10th grade educational levels. The author distribution varied, with neurologists being the most common. A significant proportion of the websites were for profit. Treatment of attacks and preventive measures were frequently mentioned, but some important treatments, such as greater occipital nerve blockade, were rarely discussed. Conclusion This study highlights the low quality and reliability of online information websites on migraine treatment in Türkiye. These websites' readability level remains a concern, potentially hindering patients' access to accurate information. This can be a barrier to migraine care for both patients with migraine and the physician. Better supervision and cooperation with reputable medical associations are needed to ensure the dissemination of reliable information to the public.